Konseling Kelompok Berbasis Cognitive Behavior Therapy untuk Mengatasi Stres Akademik Mahasiswa dalam Penyusunan Skripsi - Ade Andriyan; Muhammad Yamin; Muhammad Amin Arqi; Lalu Raftha Patech (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Academic stress is a psychological condition that occurs when students perceive academic demands as exceeding their personal capacity to cope. This problem is commonly experienced by final-year students who are writing undergraduate theses, as they face pressure related to research completion, supervision, academic expectations, time management, and future uncertainty. This study aimed to describe the implementation of group counseling using a Cognitive Behavior Therapy (CBT) approach to address academic stress among students writing their theses. A descriptive qualitative approach with a case study design was employed. The counseling program was conducted from September 12 to July 24, 2024, involving six final-semester students who participated in four structured counseling sessions. Data were collected through observation, counseling records, interviews, and documentation of participants’ experiences during the thesis-writing process. The findings showed that students experienced academic stress in physical, emotional, cognitive, and behavioral forms, including fatigue, anxiety, self-blame, lack of confidence, procrastination, and difficulty initiating thesis-related tasks. The CBT-based group counseling process helped students identify irrational thoughts, maladaptive beliefs, and negative emotional responses related to thesis completion. Through self-management techniques, including self-monitoring, stimulus control, and self-reinforcement, students were encouraged to regulate their thoughts, emotions, and behaviors more adaptively. The findings indicate that CBT-based group counseling can support students in understanding the sources of academic stress, restructuring negative thoughts, and developing more effective coping strategies. This study provides practical implications for university counseling services and study programs in designing structured psychosocial support for final-year students to reduce academic stress and improve thesis completion readiness.